1992
DOI: 10.1007/bf00689964
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of liposome-entrappedcis-bis-neodecanoato-trans-R,R-1,2-diaminocyclohexane platinum(II) and cisplatin given i.v. and i.p. in the rat

Abstract: The pharmacokinetics of liposome-entrapped cis-bis-neodecanoato-trans-R,R-1,2-diaminocyclohexane platinum(II) (L-NDDP) and cisplatin (CDDP) were studied after i.v. and i.p. administration of an equimolar dose (11 and 5 mg/kg for L-NDDP and CDDP, respectively) in the rat. The systemic absorption following i.p. administration was faster in rats receiving CDDP than in those receiving L-NDDP. Peak serum platinum (Pt) levels were observed at 30 min and 12 h after the i.p. administration of CDDP and L-NDDP, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…These studies have demonstrated a significantly prolonged retention time of the liposome-encapsulated chemotherapeutic agents in the peritoneum. These studies support the hypothesis that there is a marked pharmacological advantage for the treatment of intraperitoneal malignancies by encapsulating the intraperitoneally administered chemotherapeutic agent in a liposome (Vadiei et al, 1992;Daoud, 1994). Other studies demonstrate an improved toxicity profile.…”
Section: Liposome Delivery To Peritoneum and Associated Lymph Nodes 13supporting
confidence: 69%
See 1 more Smart Citation
“…These studies have demonstrated a significantly prolonged retention time of the liposome-encapsulated chemotherapeutic agents in the peritoneum. These studies support the hypothesis that there is a marked pharmacological advantage for the treatment of intraperitoneal malignancies by encapsulating the intraperitoneally administered chemotherapeutic agent in a liposome (Vadiei et al, 1992;Daoud, 1994). Other studies demonstrate an improved toxicity profile.…”
Section: Liposome Delivery To Peritoneum and Associated Lymph Nodes 13supporting
confidence: 69%
“…In the last decade, research has been performed with intraperitoneally administered liposome-encapsulated anticancer agents (Malik et al, 1991;Vadiei et al, 1992;Daoud, 1994;Sharma et al, 1996Sharma et al, , 1997. These studies have demonstrated a significantly prolonged retention time of the liposome-encapsulated chemotherapeutic agents in the peritoneum.…”
Section: Liposome Delivery To Peritoneum and Associated Lymph Nodes 13mentioning
confidence: 99%
“…4 Preclinical data showed that L-NDDP had a dramatically different biodistribution from that of NDDP, with accumulation of platinum in major organs, such as the liver, spleen, and lymph nodes. 43,44 In a preclinical toxicology and antitumor activity study, it was found that L-NDDP did not induce nephrotoxicity, but myelosuppression was the Abbreviations: MTD, maximum tolerated dose; NDDP, cis-bis-neodecanoato-trans-R,R-1,2-diaminocyclohexane platinum (II); DMPC, 1,2-dimyristoyl-sn-glycero-3-phosphocholine; DMPG, 1,2-dimyristoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (sodium salt); HSPC, hydrogenated soy phosphatidylcholine; DSPe-PeG2000, 1,2-distearoyl-snglycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (ammonium salt); DPPG, 1,2-dipalmitoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (sodium salt); NA, not available; DSPC, 1,2-distearoyl-sn-glycero-3-phosphocholine; DSPG, 1,2-distearoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (sodium salt); min, minutes. …”
Section: Clinically Evaluated Liposomal Formulations For Platinum Drumentioning
confidence: 99%
“…MLV composed of dimyristoyl phosphatidylcholine (DMPC) and dimyristoyl phosphatidylglycerol (DMPG) (ratio 7 : 3) containing the lipophilic platin cis-bis-neodecanoato trans-R,R-1,2 diaminocyclohexane platinum (II) (NDDP) have been shown to yield equivalent or increased tumours levels compared with unencapsulated cisplatin after intravenous administration . In addition, this agent appeared to have particularly attractive pharmacokinetics after intraperitoneal injection (Vadiei et al 1992), which has promoted its use as an intracavitary agent in patients with malignant eOE usions in early clinical trials (see below).…”
Section: Pre-clinical and Clinical Studiesmentioning
confidence: 99%
“…Other signi® cant toxicities included nausea, vomiting and diarrhoea, but there was no evidence of nephrotoxicity or ototoxicity. The favourable pharmacokinetics documented after intraperitoneal administration in mice (Vadiei et al 1992) have prompted studies of locoregional administration of this agent in patients with malignant eOE usions (Perez-Soler et al 1997, 1999. In the ® rst study, 21 patients with non-loculated malignant pleural eOE usions due to lung cancer, ovarian cancer and mesothelioma were treated with escalating doses of intrapleural liposomal NDDP (Perez-Soler et al 1997).…”
Section: Liposomal Daunorubicin (Daunoxome)mentioning
confidence: 99%